Marketing Strategy for Mitraguna Products at Syariah BankIndonesia Pekanbaru Harapan Raya Branch Office - Muhammad Zidan Abiyyu; Muhammad Syahrullah (Universitas Sains dan Teknologi Komputer, 2026)
Bank Syariah Indonesia offers Mitraguna Financing, a multipurpose sharia-based financing product designed to meet the consumption needs of employees and retirees through transparent, fair, and interest-free mechanisms. In the increasingly competitive banking industry, an effective marketing strategy is required not only to increase financing distribution but also to strengthen public understanding of sharia financial products. This study aims to analyze the marketing strategy applied to the Mitraguna Financing product at Bank Syariah Indonesia KC Pekanbaru Harapan Raya and to identify its implementation in branch-level operational activities. This research used a descriptive qualitative approach. Data were collected through direct observation during an internship program, informal interviews with employees involved in marketing and financing activities, and documentation studies of relevant company documents. The findings show that Mitraguna Financing's marketing strategy is implemented through the 7P marketing mix, comprising product, price, place, promotion, people, process, and physical evidence. Personal selling, transparent information delivery, customer relationship management, and the use of digital services such as BYOND support the effectiveness of the marketing process. However, challenges remain, including limited customer understanding of sharia financing, administrative constraints, and potential data input errors. This study implies that strengthening Sharia financial literacy, optimizing digital promotion, and improving human resource competence are necessary to enhance the effectiveness of Mitraguna Financing marketing.